Optimization modeling for conjunctive use planning of surface water and groundwater for irrigation - Singh, A.; Panda, S.N.; Saxena, C.K.; Verma, C.L.; Uzokwe, Veronica N.E.; Krause, P.; Gupta, S.K. (American Society of Civil Engineers, 2016)
The continuous increase in global population and simultaneous decrease in good-quality water resources emphasize the need of conjunctive use of groundwater and surface-water resources for irrigation. The optimal allocation of water resources can be achieved by employing an appropriate optimization technique. This paper presents an overview of the different programming techniques used for the conjunctive use planning and management of irrigated agriculture. Past papers on the applications of different programming techniques for the conjunctive use of different water sources are grouped into four categories: linear programming, nonlinear programming, dynamic programming, and genetic algorithms. Conclusions are provided based on this review, which could be useful for all stakeholders.